2013
DOI: 10.5603/kp.2013.0120
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical exercise and quality of erection in men with ischaemic heart disease and erectile dysfunction subjected to physical training

Abstract: 1. In subjects with IHD and ED, erection quality is significantly correlated with exercise tolerance. 2. Exercise training had a positive effect on both exercise tolerance and erection quality but the size of these two effects was different and they ran independently of each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 16 publications
3
29
1
6
Order By: Relevance
“…Another recent study demonstrated that higher exercise tolerance is also an important factor for satisfactory sexual activity, and the quality of erections in men with CAD and ED. 1 These findings are similar to those of the present study; subjects with higher functional capacity reported lower ED, supported by the significant negative correlation between 6-minute walk distance and ED identified through the IIEF questionnaire.…”
Section: Discussionsupporting
confidence: 93%
“…Another recent study demonstrated that higher exercise tolerance is also an important factor for satisfactory sexual activity, and the quality of erections in men with CAD and ED. 1 These findings are similar to those of the present study; subjects with higher functional capacity reported lower ED, supported by the significant negative correlation between 6-minute walk distance and ED identified through the IIEF questionnaire.…”
Section: Discussionsupporting
confidence: 93%
“…The studies were performed in three continents: five from Europe,18 19 21 23 24 one from Asia20 and one in Africa 22. Follow-up ranged from 8 weeks to 2 years.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The mean age among participants ranged from 43 to 69 years. The mean severity of erectile dysfunction was identified as severe,20 24 moderate19 22 and mild to moderate18 21 23 according to the IIEF-5 classification of severity 10. Predisposing factors for erectile dysfunction also varied among studies: one described no predisposing conditions,24 two enrolled radical prostatectomy20 and invasively treated patients with ischaemic heart disease18, and the remainder included patients with one or more cardiovascular risk factors alone 19 21–23…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations